2013
DOI: 10.1021/nn305193d
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber-Based Delivery of Therapeutic Peptides to the Brain

Abstract: The delivery of therapeutic peptides and proteins to the central nervous system is the biggest challenge when developing effective neuropharmaceuticals. The central issue is that the blood-brain barrier is impermeable to most molecules. Here we demonstrate the concept of employing an amphiphilic derivative of a peptide to deliver the peptide into the brain. The key to success is that the amphiphilic peptide should by design self-assemble into nanofibers wherein the active peptide epitope is tightly wrapped aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 52 publications
(87 reference statements)
4
74
0
Order By: Relevance
“…By employing probe sonication we reduced to a few minutes the time needed for the self-assembly process to take place. As previously reported by Mazza et al, 15 this strategy can be employed to prepare an aqueous dispersion of short nanofibers below one micron (length range). PNFs were prepared by using two designer peptide amphiphiles in isotonic media (5% dextrose) at a concentration of 1 mg mL -1 and as a result of sonication we could observe by TEM the formation of cylindrical nanofibers as depicted in Fig.1A, C and D, F.…”
Section: Ivis Imagingmentioning
confidence: 81%
“…By employing probe sonication we reduced to a few minutes the time needed for the self-assembly process to take place. As previously reported by Mazza et al, 15 this strategy can be employed to prepare an aqueous dispersion of short nanofibers below one micron (length range). PNFs were prepared by using two designer peptide amphiphiles in isotonic media (5% dextrose) at a concentration of 1 mg mL -1 and as a result of sonication we could observe by TEM the formation of cylindrical nanofibers as depicted in Fig.1A, C and D, F.…”
Section: Ivis Imagingmentioning
confidence: 81%
“…The amphiphilic nature of the peptide prodrug is hypothesised to assist in its transcytosis across the BBB endothelial cells. We have also shown that a lipidised peptide prodrug -O-tyrosinyl 1 palmitate-DAlanine 2 -leucine 5 -enkephalin (palmitoyl dalargin) forms nanofibres [9] and that these naked palmitoyl dalargin nanofibres deliver palmitoyl dalargin to the brain on intravenous injection, resulting in dalargin anti-nociceptive activity [10]. Dalargin alone, on intravenous injection, is not detected in the brain and is not active.…”
Section: Introductionmentioning
confidence: 95%
“…1). Peptide amphiphiles have been shown to self assemble into nanofibres [9,10,23] and peptide nanofibres arise from the hydrophobic association of the peptide's hydrophobic units and the hydrogen bonding of the peptide amino acids in the peptide backbone to form a beta sheet, with the peptide beta sheet wrapping tightly around the peptide nanofibre shaft [10]. The inclusion of GCPQ coats the nanofibres, as evidenced by the shift in zeta potential from a negative to a positive value on inclusion of GCPQ (Table 1).…”
Section: Peptide Nanofibre Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The dalargin derivative had improved uptake, pharmacodynamic effects, and reduced clearance from the brain parenchyma. In this instance, the prolonged activity of palmitoyl-dalargin nanofibers was associated with the slow dissociation of the drug from agonist receptors, and slow conversion of the prodrug to dalargine by plasma esterases [133]. Mazza et al, showed that nanofibers of palmitoyl-GGGAAAR and palmitoyl-GGGAAAKRK in 5% dextrose could be used to transport molecules to the brain.…”
Section: Drug Delivery Applications Of Self-assembled Peptides 41 Dmentioning
confidence: 99%